Discovery of Molidustat (BAY 85‐3934): A Small‐Molecule Oral HIF‐Prolyl Hydroxylase (HIF‐PH) Inhibitor for the Treatment of Renal Anemia. (14th April 2018) - Beck, Hartmut; Jeske, Mario; Thede, Kai; Stoll, Friederike; Flamme, Ingo; Akbaba, Metin; Ergüden, Jens‐Kerim; Karig, Gunter; Keldenich, Jörg; Oehme, Felix; Militzer, Hans‐Christian; Hartung, Ingo V.; et al.
Abstract: Small‐molecule inhibitors of hypoxia‐inducible factor prolyl hydroxylases (HIF‐PHs) are currently under clinical development as novel treatment options for chronic kidney disease (CKD) associated anemia. Inhibition of HIF‐PH mimics hypoxia and leads to increased erythropoietin (EPO) expression and subsequently increased erythropoiesis. Herein we describe the discovery, synthesis, structure–activity relationship (SAR), and proposed binding mode of novel 2, 4‐diheteroaryl‐1, 2‐dihydro‐3 H ‐pyrazol‐3‐ones as orally bioavailable HIF‐PH inhibitors for the treatment of anemia. High‐throughput screening of our corporate compound library identified BAY‐908 as a promising hit. The lead optimization program then resulted in the identification of molidustat (BAY 85‐3934), a novel small‐molecule oral HIF‐PH inhibitor. Molidustat is currently being investigated in clinical phase III trials as molidustat sodium for the treatment of anemia in patients with CKD. Abstract : Restoring EPO production : Insufficient erythropoietin (EPO) synthesis can be the cause of renal anemia in patients with chronic kidney disease (CKD). Here we report the discovery of molidustat, a novel, oral, selective hypoxia‐inducible factor prolyl hydroxylase (HIF‐PH) inhibitor, which offers an alternative approach to the treatment of renal anemia. Molidustat has entered phase III clinical trials for the treatment of anemia in patients with CKD.